2015
DOI: 10.3109/10717544.2015.1116027
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal delivery of oxybutynin chloride proniosomal gels for the treatment of overactive bladder

Abstract: Context: Overactive bladder (OAB) is a common problem and anticholinergic drugs are first-line therapy, but they have side effects. Objective: Development of oxybutynin chloride (OC) proniosomal gels and analyses of its efficacy for OAB treatment. Materials and methods: Phase separation coacervation was used to prepare proniosomal gels using various non-ionic surfactants, lipids, soy lecithin and isopropyl alcohol. Gels were characterized with regard to entrapment efficiency (EE), vesicle size, surface morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Elshafeey et al developed controlled release of the drug into the systemic circulation with the use of TT microemulsion, which was advantageous in prevention of nocturnal enuresis with improvement in patient compliance (16). Similar studies of both oxybutynin and TT proniosomal gel were reported by our group to be suitable for transdermal route, which reduced the dry mouth eff ect compared to the oral route in our earlier studies (17,18). The drug had not been explored for transdermal delivery as a patch and this is the fi rst study that analyses the effi cacy of this formulation.…”
supporting
confidence: 56%
See 2 more Smart Citations
“…Elshafeey et al developed controlled release of the drug into the systemic circulation with the use of TT microemulsion, which was advantageous in prevention of nocturnal enuresis with improvement in patient compliance (16). Similar studies of both oxybutynin and TT proniosomal gel were reported by our group to be suitable for transdermal route, which reduced the dry mouth eff ect compared to the oral route in our earlier studies (17,18). The drug had not been explored for transdermal delivery as a patch and this is the fi rst study that analyses the effi cacy of this formulation.…”
supporting
confidence: 56%
“…The dermal side of the skin just touched the receptor liquid surface horizontally to allow drug permeation. The receptor compartment temperature, volume of sample collection and method of analysis were similar to the in vitro release study (17,20). The Internat ional Medical University (IMU) Research Ethics Committ ee (B0109_ Res182012) approved the procedures and animal care for the experiments undertaken in this project including pharmacological experiments.…”
Section: In Vitro Permeation Studiesmentioning
confidence: 92%
See 1 more Smart Citation
“…LC have the ability to form an organized mesophase exhibiting both crystalline solid and liquid properties [12]. The LC system has unique microstructure and physicochemical properties, whereby it can potentially solubilize oil and water-soluble compounds and thus can be used as a drug carrier system for both hydrophilic and hydrophobic drugs [13,14]. The incorporation of drugs in liquid crystals irrespective of their relative affinity towards hydrophilic or hydrophobic solvents is exploited in the field of biological sensing and drug delivery for various drug categories and formulations, i.e., analgesics, anti-cancer agents, drugs for liver diseases, anti-asthmatic drugs, nanoparticles formulations, and others [15].…”
Section: Introductionmentioning
confidence: 99%
“…Proniosomes were prepared by a coacervation phase separation method (Gadekar et al, 2013;Ramkanth et al, 2014;Rajabalaya et al, 2015). Precisely weighed amounts of surfactant, soya lecithin, cholesterol, and drug were taken in a clean and dry wide mouthed glass vial of 5.0 ml capacity and absolute ethanol (0.25 ml) was added to it.…”
Section: Preparation Of Lacidipine Proniosomesmentioning
confidence: 99%